Reproductive ecology of the catfish, Hassar affinis (ACTINOPTERYGII: DORADIDAE), in three lakes of the Pindaré-Mearim Lake System, Maranhão (Revista Ciência Agronômica, 2017)
Reproductive biology affords fundamental features for the establishment of protective measures for fish. The aimof the present work therefore was to determine the reproductive features of the catfish, Hassar affinis, known locally as bico-deflor, in three lakes of the Pindaré-Mearim Lake System, in the state of Maranhão, with the aim of subsidising the closed season.Monthly collections were carried out between July 2014 and July 2015, when 206 individuals were sampled from Lake Aquiri(LA), 247 from Lake Cajari (LC), and 126 from Lake Viana (LV). In the laboratory, each individual was weighed and measured;a ventral longitudinal incision was then made in order to observe the gonads macroscopically. They were then fixed in Bouin’ssolution for microscopic analysis and in Gilson’s solution for an analysis of fecundity. Positive allometry was recorded at thethree study sites. The sex ratio for the total period was 3.29F:1M (LA), 2.43F:1M (LC) and 2.15F:1M (LV). Mean length at firstsexual maturity was estimated at 10.60 cm (LA), 10.84 cm (LC) and 11.12 cm (LV). The period from March to May was definedas the breeding season for this species in the three lakes. Mean absolute fecundity was 21,634 oocytes (LA), 16,357 oocytes (LC)and 25,898 oocytes (LV). The information obtained through this study indicates that, in addition to being important spawningareas, the three lakes are interconnected in relation to the migratory dynamics of H. affinis, so it is necessary to arrive at a modelthat would satisfactorily cover the three lakes, considering that the dam has a negative effect on Lake Viana.